(3GdfXGe GdbGfhfi dJOGhd GdChQGb GdeGdjI ai GdHhQUI (B/ s - (3aJMi YHOGdQMef CMeO GdThjWQs; (3CMeO aGQhb hTGMi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JOGhd GdChQGb GdeGdjI gh Cge eG jJe OGNd GdHhQUI(B: (3agh GdZQV GdPi ef CLdg CfTFJ GdHhQUI(B: (3h gh eG JSYi Edjg GdTQcGJ dJMbjb GfJTGQ UjJgG h PjGY TgQJgG(B: (3h jgOa ef NdGdg GdeSJKeQhf Edi JMbjb GdQHM hfeGA eONQGJge(B: (3dPdc cGf GdHMK aj gPg GdOQGSI Yf GdCMcGe GdbGfhfjI GdJj JYfi HJfXje gPg GdYedjI ai Shb GdHhQUI GdeUQjI(B: (3h GdJi jXgQ ef NdGdgG Cf GdhSjW ai GdChQGb GdeGdjI gh UGMH GdOhQ GdeMhQj hGdgGe GdPi HOhfg jHWd GdJOGhd(B: (3hMdbI GdhUd Hjf GdHGFY h GdeTJQj(B: (3h HfGA Ydi GdJRGeGJg Je GYJHGQg hcjdkG ef fhY NGU(B: (3h HQZe Cf GdhSjW gh JGLQ eMJQa(B: (3EdG Cfg jfHZj GdJfHjg Ydi GdJCcO ef hLhO Kef GdChQGb GdeGdjI bHd TQGFgG(B: (3egeG cGfJ edGAI GdYejd(B: (3h HZV GdfXQ(B: (3YeG EPG cGf GdYejd aQOkG Ce TQcI(B: (3hcPdc GdJfHjg Ydi Cfg jSeM ddhSjW JLGhR ChGeQ GdYejd Ef cGf ajg eUdMI NGdUI ddYejd(B: (3HGdEVGaI Edi Cf Ydi GdeTQY eQGLYI CMhGd jfHZj ajgG GSJKfGA GbJUGQ GdJOGhd Ydi GdhSjW(B: (3ai MGdGJ efgG GdgHI(B: (3h GdeYGedGJ GdEQKjI(B: (3h GdJfGRd Hjf TQcJjf Jedc EMOGgeG (B20% (3ef QCS eGd GdCNQi(B: (3h fbd GdedcjI HCeQ GdeMceIs
The securities' trading is the most important thing within the stock market. It is the main purpose of the stock market and established for. Companies seek to achieve the spread of their reputation and get fame. Investors aim to achieve profit and develop their savings. This study focuses on the legal provisions which organizing the process on the Egyptian stock market. It showed that the fundamental role in stock market is in broker's hands because without him the transaction will considered null, and he is the link between the seller and the buyer. Based on his obligations, we can consider him as a special kind agent. Although the broker is a professional trader, it should be taken in mind that the value of the securities must be deposited in advance before purchase whatever the customer's solvency, regardless of whether the customer was an individual or a company. Moreover the broker is allowed to bypass the customer's orders if there is a pure interest to the client. Legislator should review some provisions about restricted limitation of brokers in certain cases such as donation, legacy, waiver between two companies one of them owns 20% of the other's capital, and transfer by court order
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B263-275s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3GdChQGb GdeGdjIs; (3GdJOGhds; (3GdhSjWs; (3GdhSjWs; (3GdGSges; (3GdShbs; (3GdGcJJGHs; (3GdGaUGMs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs